(untitled) (Research, Society and Development, 2022)
Introduction: The present work addresses the origin, cultivation, properties and characteristics of the tucumã fruit, analyzing the main benefits that the tucumã fruit can bring in the prevention of dyslipidemias as well as showing its forms of consumption on a daily basis and the relevance of the decrease on dyslipidemias through a nutritionally based diet and professional monitoring. Objective: aims to help prevent dyslipidemia by helping lipids to function Methodology: The research chosen was bibliographic and descriptive/explanatory because it details the main nutritional qualities of the tucumã fruit and because it examines the importance of treating dyslipidemias through food. Results: Through the work, it was possible to verify in the non-pharmacological treatment that a healthy and adequate diet with nutritional monitoring, along with physical activities are the way to correct these diseases as well as the use of some medicines, in this way we can include that such indications can and should be carried out to prevent them, such as nutritional monitoring and changing bad habits. Results and discussions: According to the Brazilian Society of Cardiology (2013), dyslipidemias can be classified as primary or without apparent causes according to the level of lipid levels in the bloodstream (laboratory test), found in relation to cholesterol and to triglyceride. Conclusion: With the article, we can conclude the importance of a healthy diet based on nutrition and accompanied by nutritionists, it can reduce dyslipidemic diseases, as well as reduce their severity if well monitored and performed by the patient.